Analyzing aesthetics in the song "Golden Hour" by JVKE: A theoretical exploration - Teguh Gumilar; Andhita Zahrany Putri (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2023)
Aesthetics is a very common term. Everyone has their views because their tastes are clearly different. Aesthetics itself is the concept and principle of beauty. Beauty is a relative thing. Therefore, aesthetic views are measured through aesthetic parameters. This analysis uses a qualitative approach with the case study method. This case study is intended to find out the meaning of the song "Golden Hour" by JVKE, and the subject of this analysis is the lyrics and the music itself. The song has quite a unique character and is suitable for analysis or dissecting so that the intent of the work's creator can be conveyed. Aesthetics is the study of principles and laws that define beauty. It involves various meanings influenced by human perceptions and inherent values. This study examines the correlation between aesthetics and music, focusing on how the beauty of music communicates the feelings and sentiments of the artist to the listener. The value of beauty is decided by the perspectives of the appreciators who act as judges of the work, even though beauty itself is subjective. Therefore, aesthetics is considered to be a conceptual idea that needs concreteness. The objective of this research is to examine the song "Golden Hour" by JVKE using a technical approach, emphasizing how the musical beauty of the song influences important components of judgement, such as meaning, interpretation, expressiveness, and aesthetic qualities. Aesthetic metrics are employed to assess the levels of aesthetic quality, recognizing the subjective nature of these evaluations. Assessments can be classified into autonomic and heteronomic perspectives. A comprehensive comprehension of diverse musical components such as rhythm, melody, harmony, tempo, dynamics, and others is needed to fulfill the requirements for an aesthetic assessment of a song. The soul's destiny is intricately connected to aesthetic truths; a piece of artwork, despite its seeming materiality, depends on the act of observation and the experience of pleasure.